Human resources management in Adventist Primary Schools in South Botswana conference : challenges and possible way forward - Guzha, Machinda (Midlands State University, 2020)
This study sought to investigate Human Resource Management in Adventist Primary Schools in South Botswana Conference: Challenges and Possible Ways Forward. It is a case of two schools that are run by the South Botswana Conference of the Seventh Day Adventist Church in Botswana. The study was centred on the issues that affect the human resources in the schools hence the focal point was on collecting data from the people in the school Administration which included The Principal and all the heads of departments. The purpose of the study was to investigate challenges faced by the SBC schools in the Human Resource Management systems. It also aimed at investigating performance management and reward systems in the schools and submit recommendations to the board. This research was based on the qualitative approach and followed the case study design. The data collection instruments used included the Interviews and Questionnaires. The sample population was made up of the members of the school Administration Committee whose membership was Principals, Deputy Heads and HODs. The data that were collected were analysed and issues that were concluded indicated that there were challenges in the SBC system of schools. The details of the challenges are discussed in the whole report of the research. The conclusion and recommendations were that the Board of SBC schools needs to address some of the issues if they are to form a brand in Christian Education. The challenges that the researcher established include shortages of qualified primary school teachers in the Botswana job market, low salaries for teachers offered by the SBC schools, unclear contracts of employment, unstandardized teacher performance system, a high staff turnover and the issue of expatriate teachers’ permits. Some of the recommendations suggested include review of the teachers’ contracts of employment, reviewing of the reward system to make it more competitive and putting in place a performance management system.